(untitled) (Revista de Medicina Clinica, 2021)
It is common that in adult training, methods and approaches with own designs of school students are used, instead of using designs and approaches oriented to adults. Many education specialists agree that andragogy is not a theory, but rather an alternative to pedagogy. On the other hand, the theoretical link to practice has been a desire of all educational programs, however, the theoretical contents can be seen in a gradual and organized way, however, during practice it does not happen in such a way. For this reason, there is an urgent need to return to theoretical texts and confront them with experience, hence the importance of a self-directed education such as andragogy. In this writing we refer to these two aspects, andragogical education and learning from experience